Increased Nutrition Intake from Day 1 to Day 7 and Its Correlation with LOS in The Burn Unit of Dr. Cipto Mangunkusumo Hospital Jakarta - Sinaga, Wina; Nurul Ratna Mutu Manikam; Aditya Wardhana; Nandita Melati Putri; Lily Indriani Octovia; Akhmad Noviandi Syarif (Jurnal Plastik Rekonstruksi, 2022)
Introduction : Burn patients as well as the critically ill experience strong oxidative stress, an intense inflammatory response, and a prolonged months-long hypermetabolic and catabolic response that affect nutritional requirements. This study aimed to investigate the nutrition intake in the acute phase from day 1 to day 7 and the correlation with length of stay (LOS) in burn patients in Dr. Cipto Mangunkusumo General Hospital.Method : This cross-sectional study was conducted from January to December 2020 in the Burn Unit of Dr. Cipto Mangunkusumo General Hospital. Research subjects were burns patients who were willing to take part in this research and met the research criteria. The characteristics data included gender, age, burn area, cause of burns, body mass index, and intake analysis were obtained from medical records and were analyzed using Spearman’s correlation and linear regression.Result : A total of 68 subjects were included in this study. There was an increase in energy intake from day 1 to day 7 of 10.81 + 12.73 Kcal/kgBW. There was a significant negative weak correlation between energy changes from day-1 to day-7 and length of stay (r = -0.25, p = 0.03).Conclusion: The higher energy increases within 7 days of treatment, the shorter the LOS of burn patients. Further research is still needed to assess the components that influence nutrition intake and how they impact the clinical outcome of burn patients.